Leukemias Updates and New Insights - Guenova, Margarita; Balatzenko, Gueorgui (IntechOpen, 2015)
Hematology has constantly been advancing in parallel with technological developments that have expanded our understanding of the phenotypic, genetic, and molecular complexity and extreme clinical and biological heterogeneity of leukemias. This in turn allowed for developing more effective and less toxic alternative therapeutic approaches directed against critical molecular pathways in leukemic cells. The continuous and rather extensive influx of new information regarding the key features and underlying mechanisms as well as treatment options of leukemias requires frequent updating of this topic. The primary objective of this book is to provide the specialists involved in the clinical management and experimental research of acute and chronic leukemias with comprehensive and concise information on some important theoretical and practical developments in the biology, clinical assessment, and treatment of patients with leukemias; on specific clinical scenarios such as pregnancy or age; as well as on some molecular and pathogenetic mechanisms and their respective translation into novel therapies.